POLITICAL TERROR OF THE 1920S AND 1930S AGAINST THE SCIENTIFIC INTELLIGENTSIA OF UKRAINE IN THE PHILOSOPHICAL INTERPRETATION OF THE POLICY OF TOTALITARIANISM (Zaporizhzhia Historical Review, 2022)
The article presents an analysis of the policy of totalitarianism by the Communist Party and its leaders, namely the methods of struggle against the scientific intelligentsia. Much attention is paid to the ideological component of the struggle against the scientific intelligentsia, methods of ideological pressure against individual freedom and propaganda of the ideological justification of political repression are shown in terms of ideology and politics of that time, examples of philosophical interpretation of terror, which reached its apogee in the 1930s in Ukraine, are provided.